ACTUALIZATION OF INTEGRATED LEARNING DURING THE COVID-19 PANDEMIC IN ELEMENTARY SCHOOLS - Arrosyad, M Iqbal; Fhatri, Zonalisa (UIN Sunan Kalijaga Yogyakarta, 2022)
Integrated learning applied during the COVID-19 pandemic has advantages and problems. This study aims to explain the actualization of integrated learning during the COVID-19 pandemic in elementary schools. This research is qualitative research with a case study approach. The research subjects in this study were fourth-grade teachers and third-grade teachers at SD Negeri 5 Puding Besar, Bangka Belitung Islands Province. The data collection technique uses observation, interview, and document study techniques. The data analysis techniques used in this study are data reduction, data display, and conclusion. The results of this study are that learning is carried out with online and offline systems coming home for students who have problems related to cellphones, signals, and packages, the learning planning model (RPP) in online learning during the COVID-19 pandemic contains parts of the elements including 1) Identity Consists Of; 2) Learning Scenarios, and 3) Assessment. The inhibiting factor is related to learning devices that require internet signals and packages. The supporting elements for existing devices such as gadgets, WhatsApp applications, google meet, and zoom become applications to facilitate implementation of distance or online learning. This finding is expected to inspire the implications of integrated learning during the COVID-19 pandemic